Translation Techniques Of English Translation On Umpasa And Umpama In Batak Toba Wedding Ceremonies - B. Sinaga, Berlianta; Octaviana, Yessy; Sitorus, Nurhayati (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This research investigates the complex interplay between traditional oral literature and digital linguistics. Specifically, it analyzes the translation techniques applied to Umpasa and Umpama the ritualistic proverbs and poetry of the Batak Toba culture translated into English within the socio-cultural context of traditional wedding ceremonies. The study aims to describe the representation of cultural meanings and evaluate the maintenance or shift of traditional values when processed through the Large Language Model, Gemini AI. Adopting a descriptive qualitative approach, a corpus of 48 units of oral literature was meticulously collected through field observations in Samosir Regency and further validated by Raja Parhata to ensure cultural authenticity. The findings reveal 63 occurrences of specific translation techniques, with Established Equivalence emerging as the most dominant method (16 findings). This indicates a strategic priority toward functional clarity for a global audience. The analysis concludes that while a linguistic shift from esoteric, metaphorical language to explicit meanings is inevitable, the core philosophical pillars of Batak life Hagabeon, Hamoraon, and Hasangapon remain successfully preserved in the digital translation process.